Transformation in the subsistence mode (Livelihood)1, of community families in the framework of the presence and action of Inkabor and the development projects of the National Reserve Salinas Aguada Blanca - Felipe Mario Zapata-Delgado (2019)
Privileging the Peruvian government, development as an indispensable economic factor in the improvement of the economic conditions of the most needy in rural areas, has created a wave of transformations within the subsistence system in rural communities, which have generated a greater poverty and especially inequitable situations of life among the community members. The subsistence based on the production and consumption of the communal families, revolvesaround the domestic unit and the production area; It has as factors for its permanence and reproduction the process of combining Andean elements such as reciprocity, redistribution, balance and control of ecological floors; through particular forms that respond to their own contexts, where interactions, articulations and their own dynamics occur; In addition to assuming foreign elements such as the mercantilist system (19th century) that allowed it to be combined, adapted and continue to reproduce the subsistence. The “developmentalist” impacts in both mining and development projects have generated a transformation in the subsistence and representations of the high Andean communities since these have been articulated through the work or provision of services to mining companies and in other cases they have assumed the development projects that have changed their orientations and perceptions around productionand consumption. The Salinas Huito community is framed in this transformation, first of all being a pastoral society, it became a peasant community, which, being part of the Salinas Aguada Blanca National Reserve, had project impacts to be sustainable in this ANP; In addition, the entry of the INKABOR mining company allowed its articulation through the provision of services and goods to this company, which led to a radical transformation in the traditional way of subsistence Precisely this research tries to recognize these transformations within the communal families, in addition to evidencing the new representations that have caused these impacts, in their ways of life, orientations, symbols and differentiations within the community, in addition to presenting a “ new community family ”, where the city-countryside is undifferentiated, which seeks the production and reproduction of the subsistence mode, permanently.